Distribusi Vertikal Sifat Kimia Tanah pada Tegakan Tanaman Cengkeh, Pala, dan Kelapa - Adnan Sofyan; Asrul Dedy Ali Hasa; Idris Abdul Rachman; Nurul Aini Tangge; Ayulenda Makalu (Lembaga Pengembangan Kinerja Dosen, 2026)
The study examines the vertical distribution of soil chemical properties under clove (Syzygium aromaticum), nutmeg (Myristica fragrans), and coconut (Cocos nucifera) stands in Togafo Village, West Ternate District. It aims to analyze how different plantation vegetation types affect soil fertility and nutrient stratification across soil depths. A survey method was used by collecting soil samples from three plantation stands at two depth intervals, 0–30 cm and 30–60 cm. The analyzed soil parameters included pH, organic carbon, total nitrogen, carbon-to-nitrogen (C/N) ratio, and available phosphorus. Data were analyzed descriptively and supported by the Soil Stratification Ratio (SSR). The results showed that soil pH ranged from 6.15 to 6.68, indicating slightly acidic to neutral conditions. Organic carbon ranged from 1.57% to 2.73%, total nitrogen from 0.09% to 0.22%, C/N ratio from 9 to 22, and available phosphorus from 10.00 to 18.75 ppm. Higher organic carbon, nitrogen, and phosphorus contents were found in the 0–30 cm layer than in the 30–60 cm layer. Clove stands showed the highest surface nutrient accumulation. These findings indicate that vegetation type influences soil nutrient stratification, with clove plantations better maintaining soil fertility.